INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM MELALUI BUDAYA HARMONISASI DI SMP NURUSSHIBYAN PAGUYANGAN - Aenul Yaqin, Muhammad; Nurfuadi, Nurfuadi (Raudhah - Proud To Be Professional, 2024)
Islamic religious education is an important aspect in forming the character of Muslim individuals. Through Islamic religious education, a person can gain a deep understanding of Islamic teachings and the values contained therein. However, just having knowledge of Islamic teachings is not enough to form good character. It is important to internalize these values so that they can be applied in everyday life. Every human being living in the universe desires harmony. This harmony has been regulated in religion, where religion calls on its owners to always live in peace, help each other, be tolerant and full of compassion. The purpose of this research is to find out how to internalize Islamic religious education values through harmonized culture in daily and weekly programs at Nurusshibyan Paguyangan Middle School. This research uses a qualitative descriptive method with field research. Data collection techniques use observation, interviews and documentation. The results of this research show that the internalization of the values of Islamic religious education through a culture of harmonization in daily and weekly programs at Nurusshibyan Paguyangan Middle School include, istiqomah, responsibility, tawadlu (politeness), patience, mutual help, friendship and mutual cooperation contained in activities related to Allah SWT (hablumminallāh), relationships with humans (hablumminannās) and relationships with nature.